2021
DOI: 10.3389/feart.2021.671801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solar Wind on Secondary Cosmic Rays and Atmospheric Electricity

Abstract: A relationship between the heliospheric magnetic field, atmospheric electric field, lightning activity, and secondary cosmic rays measured on the high mount of Lomnický Štít (2,634 m a.s.l.), Slovakia, during the declining phase of the solar cycle 24 is investigated with a focus on variations related to solar rotation (about 27 days). The secondary cosmic rays are detected using a neutron monitor and the detector system SEVAN, which distinguishes between different particles and energies. Using spectral analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Some local previous studies based on thunder days, such as that of Aniol (1952) in Germany, suggest that this may not be the case. Similarly, Chum et al (2021) 285 identified a solar rotation in lightning occurrence for Central Europe and the period 2016-2019. However, extending their study to a longer time interval revealed that the periods observed for lightning occurrence and solar wind are generally asynchronous, although they may be close together.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some local previous studies based on thunder days, such as that of Aniol (1952) in Germany, suggest that this may not be the case. Similarly, Chum et al (2021) 285 identified a solar rotation in lightning occurrence for Central Europe and the period 2016-2019. However, extending their study to a longer time interval revealed that the periods observed for lightning occurrence and solar wind are generally asynchronous, although they may be close together.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, Schlegel et al (2001) showed that cross-correlation coefficients might differ considerably when using lightning counts from those using only number of thunder days as has been done in the past. Number of studies have also documented that lightning activity can be partially modulated on shorter time scale by the solar rotation, the solar wind and the polarity of the heliospheric magnetic field, HMF (Chronis 2009;Owens et al, 2014;Scott et al, 2014;45 Owens et al, 2015;Miyahara et al, 2018;Chum et al, 2021). Statistical studies by Voiculescu and Usoskin (2012) and Voiculescu et al (2013) showed that solar activity might impact cloud cover in specific regions rather than globally.…”
Section: Introductionmentioning
confidence: 99%
“…He argues that ions produced by cosmic rays are a source of aerosols and become a center of condensation, leading to the creation of clouds (Arnold, 2008). The correlation between galactic cosmic rays and cloud cover on an 11-year solar cycle basis was shown by carslaw et al (2002), Marsh andSvensmark (2003), andChum et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Agrawal [4] postulated the occurrence of a 22year tweak as a result of the extreme inversion of the Sun's attractive field, which occurred in 1969-1970 [10]. Many workers have outlined a few study efforts to clarify the long-term Cosmic beam strength variation with regard for a part of the time lag between sunspot numbers [10,7,5,11]. An effort was made to clarify the long-term management of the astronomical beam strength using a novel balancing parameter [12,13].…”
Section: Introductionmentioning
confidence: 99%